2015
DOI: 10.1128/aem.02076-15
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Diversities of Astroviruses and Noroviruses in Wastewater Treatment Plant Effluents by a High-Throughput Sequencing Method

Abstract: cAlthough clinical epidemiology lists human enteric viruses to be among the primary causes of acute gastroenteritis in the human population, their circulation in the environment remains poorly investigated. These viruses are excreted by the human population into sewers and may be released into rivers through the effluents of wastewater treatment plants (WWTPs). In order to evaluate the viral diversity and loads in WWTP effluents of the Paris, France, urban area, which includes about 9 million inhabitants (appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 60 publications
1
34
0
3
Order By: Relevance
“…To date, only a handful of studies have examined the genotypic diversity of viruses in wastewater, in which most used traditional Sanger sequencing/cloning methods 54 - 56 , with only two employing NGS technologies 57 , 58 . Studies by Kazama et al 57 and Prevost et al 58 applied second-generation sequencing technologies (pyrosequencing) to characterise norovirus diversity in waste water, which was then compared with the diversity found in clinical samples. A French study also identified a total of 16 norovirus GII genotypes of which GII.4 (86% Sydney 2012 variant) was the most prevalent in both sample types between May 2013 and May 2014 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a handful of studies have examined the genotypic diversity of viruses in wastewater, in which most used traditional Sanger sequencing/cloning methods 54 - 56 , with only two employing NGS technologies 57 , 58 . Studies by Kazama et al 57 and Prevost et al 58 applied second-generation sequencing technologies (pyrosequencing) to characterise norovirus diversity in waste water, which was then compared with the diversity found in clinical samples. A French study also identified a total of 16 norovirus GII genotypes of which GII.4 (86% Sydney 2012 variant) was the most prevalent in both sample types between May 2013 and May 2014 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Kazama et al 57 and Prevost et al 58 applied second-generation sequencing technologies (pyrosequencing) to characterise norovirus diversity in waste water, which was then compared with the diversity found in clinical samples. A French study also identified a total of 16 norovirus GII genotypes of which GII.4 (86% Sydney 2012 variant) was the most prevalent in both sample types between May 2013 and May 2014 58 . In contrast to our study, Prevost et al 58 found a strikingly different distribution of norovirus diversity between waste water and clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…NGS has also increased the discovery rate of human-pathogenic viruses in feces (39) and has revealed that culture-based enrichment can indeed alter the taxonomic profiles of environmental samples (40). Recently, NGS approaches have been described that examine the diversity of adenovirus (42), norovirus (43), and astrovirus (43) in sewage. Those studies highlighted the utility NGS approaches for community-wide enteric virus surveillance and offered advantages over Sanger sequencing, which provides information only on the dominant circulating strain (42), and can facilitate identification of virulent recombinant virus strains that may negatively impact public health (43).…”
mentioning
confidence: 99%
“…Due to the differences in viral concentration method, primer pair and sample volume, the detection rate of classic HAstVs in sewage varies greatly (Prevost et al . ). In this study, all detected sewage samples were positive for classic HAstVs, suggesting a high HAstVs prevalence and a large number of infected individuals in the study area.…”
Section: Discussionmentioning
confidence: 97%